Предмет: Математика,
автор: sansit2010
−6(2 – 2х) = 2(х – 3) + 3
Ответы
Автор ответа:
1
Ответ:
Фото прикрепил
Пошаговое объяснение:
Приложения:
![](https://files.topotvet.com/i/7de/7de8561933a0924b3cec34a2459a3daa.png)
Автор ответа:
1
Пошаговое объяснение:
−6(2 – 2х) = 2(х – 3) + 3
- 12 + 12x = 2x - 6 +3
12x-2x=-6+3+12
10x=9
x= 9/10
ilyagamer02:
У меня тоже самое!
Похожие вопросы
Предмет: Русский язык,
автор: arina2185988
Предмет: Русский язык,
автор: Аноним
Предмет: Английский язык,
автор: alena2355
Предмет: Математика,
автор: влто
Предмет: Литература,
автор: миникотик56